2010
DOI: 10.3109/10428190903585286
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase I clinical and biologic study of two schedules of sorafenib in patients with myelodysplastic syndrome or acute myeloid leukemia: a NCIC (National Cancer Institute of Canada) Clinical Trials Group Study

Abstract: Sorafenib is a small molecule inhibitor of RAF kinase, VEGFR-2, c-KIT, and FLT3. In this randomized phase I study, eligible patients had relapsed/refractory acute myeloid leukemia (AML), and one prior induction regimen, or were age >65 with untreated myelodysplastic syndrome (MDS) or secondary AML. Sorafenib was given orally for 28 days (cont) or 14 days (int) every 4 weeks at three dose levels (100, 200, and 400 mg BID); 300 mg cont was also tested. Forty-two patients were enrolled (median age 71 [37-82]; pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…Due to the small number of patients with dose‐limiting toxicities reported in our original clinical trial,9 we were unable to perform an exposure‐toxicity assessment. However, in accordance with previously reported clinical trials in patients with AML, a lower dose of sorafenib is associated with enhanced tolerability 19, 20. Recently, another observational study has shown that sorafenib‐related adverse events were associated with a relatively higher exposure of the N‐oxide metabolite after 400 mg b.i.d.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the small number of patients with dose‐limiting toxicities reported in our original clinical trial,9 we were unable to perform an exposure‐toxicity assessment. However, in accordance with previously reported clinical trials in patients with AML, a lower dose of sorafenib is associated with enhanced tolerability 19, 20. Recently, another observational study has shown that sorafenib‐related adverse events were associated with a relatively higher exposure of the N‐oxide metabolite after 400 mg b.i.d.…”
Section: Discussionsupporting
confidence: 84%
“…Although sorafenib responses in FLT3-ITD AML patients are usually transient, 11,13,14,16 we and others have previously published several cases with relapsed FLT3-ITD AML who showed extended remissions under sorafenib monotherapy. 17,[18][19][20][21][22][23] This stimulated us to gain a better understanding of the value of sorafenib monotherapy in FLT3-ITD AML-in particular with respect to the circumstances where complete and long-lasting remissions may be obtained.…”
Section: Introductionmentioning
confidence: 89%
“…11 Three subsequent phase I studies underscored this evidence by demonstrating consistent activity of sorafenib in relapsed and refractory FLT3-ITD AML, while primary resistance was frequently seen in AML expressing the wild-type form of FLT3. [12][13][14] Thus, although sorafenib simultaneously blocks FLT3 and multiple other kinases, such as the serine threonine kinase Raf-1, plateletderived growth factor receptor and vascular endothelial growth factor receptor, 15 its most relevant target in AML appears to be FLT3-ITD.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib also targets FLT3-mutated AML cells, 116 and current phase-I/II trials are ongoing in AML. 117,118 Inhibitors of MEK have been developed that sensitize leukemic blast cells to other drugs, for example, arsenic trioxide and demethylating agents. [119][120][121] Current RAS pathway inhibitors probably will not fully block leukemic transformation in MLL-rearranged AML, but may have an additive effect with current treatment strategies by targeting the proliferative advantage of these leukemic cells.…”
Section: Toward Targeted Therapymentioning
confidence: 99%